(untitled) (Philadelphia, Pa., 1998)
The two volumes are generally well organized and make extensive use of tables, graphs, and algorithms to convey much of the information. The referencing and indexing are better than those of previous editions, and more comprehensive. There are rare references to literature published more recently than 1995, but some almost prophetic cautions are expressed about what is likely to come. The chapter on obesity provides a prescient warning about the lack of approval by the Food and Drug Administration of long-term fenfluramine-phentermine therapy.
Keywords: Gastrointestinal system,Liver,Hệ tiêu hóa,Gan; Diseases,Diseases,Bệnh,Bệnh